Crosstalk between autophagy and inflammatory signalling pathways: balancing defence and homeostasis - Cadwell, Ken (Nature reviews. Immunology, 2016)
Key Points The cellular degradative process of autophagy participates in multiple aspects of immunity, including cell-autonomous defence, innate immune signalling and antigen presentation. Extensive crosstalk between autophagy and inflammatory signalling cascades ensures a robust immune response towards pathogens while avoiding collateral damage to the host. Several chronic inflammatory disorders are associated with autophagy dysfunction. Pathways that induce autophagy, such as those downstream of pattern recognition receptors, are conversely subject to regulation by autophagy. Autophagy can increase and decrease different components of the same inflammatory signalling cascade in a context-dependent manner. Many immune-related functions of conserved autophagy proteins reflect non-canonical functions of the autophagy machinery, representing new opportunities for therapeutic intervention. This article provides a comprehensive overview of the general functions of autophagy in immunity, the interactions between autophagy and immune signalling pathways and the role of autophagy–immune crosstalk in multicellular immune responses and disease. Autophagy has broad functions in immunity, ranging from cell-autonomous defence to coordination of complex multicellular immune responses. The successful resolution of infection and avoidance of autoimmunity necessitates efficient and timely communication between autophagy and pathways that sense the immune environment. The recent literature indicates that a variety of immune mediators induce or repress autophagy. It is also becoming increasingly clear that immune signalling cascades are subject to regulation by autophagy, and that a return to homeostasis following a robust immune response is critically dependent on this pathway. Importantly, examples of non-canonical forms of autophagy in mediating immunity are pervasive. In this article, the progress in elucidating mechanisms of crosstalk between autophagy and inflammatory signalling cascades is reviewed. Improved mechanistic understanding of the autophagy machinery offers hope for treating infectious and inflammatory diseases.